Modern caste system in taxation - Kálmán Botond Géza; Loszkorih Gabriella; Лоскоріх Габріелла; Gabriella Loskorikh; Pataki Gábor; Потокі Габор; Gabor Pataki; Калман Ботонд Гейзо (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The article examines the modern dynamic development of taxation - one of the oldest forms of financial institutions. Taxes have existed since the very history of society. Their role is mainly to cover the financial costs incurred by the state in the performance of its public functions. Thus, they perform a redistributive function. Taxes are often considered as a form of forced alienation of the business entities results in favour of the state, and low levels of willingness to pay are common. One of the most likely reasons for this may be that the refund of taxes paid does not come immediately or within a certain forecast period, and in particular, in many cases, not even in a tangible form. Therefore, many taxpayers feel that they are paying taxes in vain. In this article, the authors examine the issue at three levels: at the level of citizens, business entities, and transnational corporations. Factors and features characterizing this group are defined at all three levels. The willingness of citizens to pay taxes is investigated based on the results of international studies devoted to the issue of tax morality in the state. The expected goal and result of this international study will be the development of a more transparent, unified tax system (where it is more difficult to avoid the tax burden). The authors analyse the willingness to pay taxes and the ways in which taxpayers try to reduce the amount before taxation, or, if possible, eliminate tax risks altogether. Individual citizens have the least prospects in this matter. The room for manoeuvre of companies is already much wider, characterized by the presence of several ways to reduce the size of tax payments at the business level. As the research shows, transnational corporations have the most opportunities in this area. The temptation to make huge profits often outweighs even basic moral considerations. Based on the obtained results, the authors formed a theory of the modern tax caste system and determined possible prospects for its further functioning.

Ebben a tanulmányban a szerzők megvizsgálják, hogy a világ egyik legrégebbi pénzügyi intézménye, az adózás hogyan alakul napjainkban. Az adók egyidősek a történelemmel. Szerepük legfőképpen az, hogy fedezzék az államnak azokat a költségeit, amelyek a közfunkciók ellátása során felmerülnek. Az adók így egyfajta újraelosztó funkciót töltenek be. Az adókat sokszor elkerülendő, szükséges rossz rendelkezésként kezelik, és gyakori az adófizetési hajlandóság alacsony szintje. Ennek egyik legvalószínűbb oka lehet, hogy a befizetett adókért cserébe nem azonnal, vagy belátható időn belül érkezik az ellenszolgáltatás, ami ráadásul sok esetben nem is kézzelfogható formában jelenik meg. Ezért érzik sokan úgy, hogy az adót a semmiért fizetik. A jelen cikkben a szerzők a kérdést három szinten vizsgálják: az állampolgárok, a vállalkozások és a multinacionális cégek között. Mindhárom szinten kutatják azokat a sajátosságokat, amelyek az adott csoportot jellemzik. Az állampolgárok adózási hajlandóságát az államokra jellemző adómorált vizsgáló nemzetközi kutatások eredményeit felhasználva vizsgálják. Ezeknek a nemzetközi kutatások várható célja és eredménye egy átláthatóbb, egységesebb (és kevésbé megkerülhető) adózási rendszer kialakulása lesz. A szerzők elemzik az adófizetési hajlandóságot és azokat a módszereket, amelyekkel igyekeznek csökkenteni a fizetendő adó mértékét, esetleg teljesen elkerülni az adófizetést. A legkevesebb lehetőséggel e téren az egyes állampolgárok rendelkeznek. A cégek mozgástere már jóval szélesebb, számos módon csökkenthető a fizetendő adó. A legmesszebbre pedig – ahogyan az ebből a tanulmányból kiderül, milyen messzire – a multinacionális cégek képesek elmenni. Az óriási profit kísértése sokszor az alapvető erkölcsi szempontokat is felülírja. Az eredmények alapján a szerzők megfogalmazzák a modern adózási kasztrendszer elméletét és kifejtik a véleményüket ezzel a rendszerrel kapcsolatban.

Резюме. У статті досліджено сучасний динамічний розвиток оподаткування - одного з найстаріших форм фінансових інституцій. Податки існують відколи існує сама історія суспільства. Їх основна роль полягає у покритті фінансових витрат держави для виконання своїх функцій. Таким чином, вони виконують перерозподільну функцію. Податки часто розглядають як форму примусового відчуження на користь держави результатів діяльності суб’єктів господарювання, що характеризується низьким рівнем готовності їх платити. Однією з найімовірніших причин цього може бути те, що зворотна компенсація за сплачені податки надходить не відразу або протягом певного прогнозованого періоду, зокрема у багатьох випадках навіть не в матеріальній формі. Тому багатьом платникам здається, що вони платять податки даремно. У цій статті автори розглядають проблему на трьох рівнях: на рівні громадян, суб’єктів господарювання та транснаціональних корпорацій. На всіх трьох рівнях визначені чинники й особливості, які характеризують дану групу. Готовність громадян платити податки досліджується за результатами міжнародних досліджень, які присвячені питанню податкової моралі у державі. Очікуваною метою та результатом цього міжнародного дослідження буде розробка більш прозорої, уніфікованої податкової системи (за якої важче уникнути податкового тягаря). Автори аналізують готовність платити податки та способи, за допомогою яких платники намагаються зменшити суму до оподаткування, або, за можливості, взагалі нівелювати податкові ризики.. Найменше перспектив у цьому питанні мають окремі громадяни. Простір для маневру компаній вже значно ширший, що характеризується наявністю кількох способів зменшення розміру податкових платежів на рівні бізнесу. Як показує дослідження, найбільше можливостей у цій сфері мають транснаціональні корпорації. Спокуса отримати величезний прибуток часто переважає навіть основні моральні міркування. На основі отриманих результатів авторами сформовано теорію сучасної податкової кастової системи та визначено можливі перспективи її подальшого функціонування.
Modern kasztrendszer az adózásban
Cучасна кастова система в оподаткуванні
https://aab-economics.kmf.uz.ua/aabe
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010508
Keywords: taxation; tax morale; state; citizens; enterprise; multinational companies; legal gap